siGCD: a web server to explore survival interaction of genes, cells and drugs in human cancers - Cui, XiuLiang; Han, Lu; Liu, Yang; Li, Ying; Sun, Wen; Song, Bin; Zhou, Wenxia; Zhang, Yongxiang; Wang, Hongyang (Briefings in bioinformatics, 2021)
It is pivotal and remains challenge for cancer precision treatment to identify the survival outcome interactions between genes, cells and drugs. Here, we present siGCD, a web-based tool for analysis and visualization of the survival interaction of Genes, Cells and Drugs in human cancers. siGCD utilizes the cancer heterogeneity to simulate the manipulated gene expression, cell infiltration and drug treatment, which overcomes the data and experimental limitations. To illustrate the performance of siGCD, we identified the survival interaction partners of EGFR (gene level), T cells (cell level) and sorafenib (drug level), and our prediction was consistent with previous reports. Moreover, we validate the synergistic effect of regorafenib and glyburide, and found that glyburide could significantly improve the regorafenib response. These results demonstrate that siGCD could benefit cancer precision medicine in a wide range of advantageous application scenarios including gene regulatory network construction, immune cell regulatory gene identification, drug (especially multiple target drugs) response biomarker screening and combination therapeutic design.